(untitled)
A method for analyzing productivity convergence based on frontier production functions is proposed. It is examined whether departures from the frontier|countrylevel inefficiencies|exhibit longrun relationships and convergence. The method is applied to 1-digit industries of 14 OECD countries from 197090. Results suggests that comovements in efficiency are concentrated between the EUcountries. Catchup is found in all but one sector. Even manufacturing, which previous studies have found not to display convergence, shows signs of catch-up. It is examined whether departures from the frontier|countrylevel inefficiencies|exhibit longrun relationships and convergence. The method is applied to 1-digit industries of 14 OECD countries from 197090. Results suggests that comovements in efficiency are concentrated between the EUcountries. Catchup is found in all but one sector. Even manufacturing, which previous studies have found not to display convergence, shows signs of catchup., address = Bonn, author = Christopher Mark Cornwell and Jens-Uwe Wächter, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = C2; O47; O57; 330; cointegration; convergence; economic growth; efficiency; productivity; technological diffusion; unit root, language = ger, number = B 07-1999, publisher = Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), series = ZEI Working Paper, title = Comovement and catch-up in productivity across sectors: Evidence from the OECD, url = https://hdl.handle.net/10419/39614, year = 1999